DEVELOPMENT OF MATHEMATICS LEARNING ACTIVITIES BASED ON CONSTRUCTIVIST THEORY EMPHASIZING ON POLYA’S PROBLEM SOLVING PROCESS WITH BRAINSTORMING TECHNIQUES ON PROBABILITY FOR MATHAYOMSUKSA 3 STUDENTS - Nancharee, Thanaporn; Viriyapong, Nongluk; Chiangpradit, Monchaya (Journal of MCU Nakhondhat, 2021)
The objectives of this research article were to: 1) develop plans for learning activities based on constructivist theory emphasizing on Polya’s problem solving process with brainstorming techniques with a require efficiency of 70/70; 2) compare the problem-solving ability using learning activities based on constructivist theory emphasizing on Polya’s problem solving process with brainstorming techniques with the 70% criterion. The research design of this study was the one group pretest-posttest design. The sample used in this study consisted of 23 Mathayomsuksa 3 students and obtained through cluster random sampling. The instruments used in the research were 20 learning activities plans, 30 items of the learning achievement test, and 5 subjective questions of the mathematical solving problem ability test. The statistics used for analyzing the collected data were percentage, mean, and standard deviation; moreover, one sample t-test was employed for testing hypotheses. The results of the study were as follows: 1) the lesson plans of the learning activities based on constructivist theory emphasizing on Polya’s problem solving process with brainstorming techniques on probability for Mathayomsuksa 3 students was 87.82/ 78.40, respectively. 2) the Mathayomsuksa 3 students who were taught by the mathematics lesson plans based constructivist theory emphasizing on Polya’s problem solving process with brainstorming techniques on probability had their scores on problem solving ability higher than the 70 percent criterion at .05 level of significance.